The Effect of Early Initiation of Breastfeeding on Uterine Contractions in the Fourth Stage of Labor - Nurus Safaah; Dyah Pitaloka (Alliance oh Health Activists (AloHA), 2020)
The touch and licking of the baby at the time of early initiation of breastfeeding will stimulate the release of the hormone oxytocin which will also affect the smooth muscle tissue of the uterus to contract, thereby strengthening uterine contractions in the fourth stage and helping to reduce bleeding after childbirth. The purpose of this study was to analyze the effect of early initiation of breastfeeding on uterine contractions in the fourth stage of labor. This study used a static group comparison design involving 10 respondents who were selected by simple random sampling technique. Respondents were divided into control group (5 people) and experimental group (5 people). Uterine contraction data were collected through observation. Data were analyzed by Fisher's exact test. Statistical test results show p value = 0.083; so it was concluded that early initiation of breastfeeding had an effect on uterine contractions in the fourth stage of labor. Keywords: early initiation of breastfeeding; uterine contractions